2007
DOI: 10.1093/annonc/mdl378
|View full text |Cite
|
Sign up to set email alerts
|

Is endoscopic ultrasound clinically useful for follow-up of gastric lymphoma?

Abstract: Although the length of follow-up cannot exclude late relapse, we think that in restaging and follow-up of gastric lymphoma, EUS seems not to be a reliable tool if it is abnormal and E-Bx still remains the gold standard. Therefore, after conventional conservative treatment, persistence of EUS abnormality with a negative histology should not be considered as a clinically relevant persistence of disease and should not be a reason for further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Overall, accuracy for determining nodal status is considered to be 56-90% [13,[26][27][28]. In use for post-treatment monitoring, EUS may appear positive long after biopsies are negative [29].…”
mentioning
confidence: 99%
“…Overall, accuracy for determining nodal status is considered to be 56-90% [13,[26][27][28]. In use for post-treatment monitoring, EUS may appear positive long after biopsies are negative [29].…”
mentioning
confidence: 99%
“…However, in other reports that correlation was much lower ranging from 33% and 54% [30,31] . Therefore, at present, EUS cannot be recommended for MALT lymphoma surveillance after treatment, and biopsies remain the only reliable proof of residual disease.…”
Section: Gastrointestinal Lymphomasmentioning
confidence: 67%
“…Interestingly, Varas et al defined, in a subset of 24 patients, an accuracy of EUS in defining T factor of 91%, whereas the usage of miniprobes has given an accuracy of 88% and this mismatch was higher in evaluating the N factor confirming the high clinical impact of EUS (Varas et al, 2006). As a general rule, EUS has entered in the clinical practice of staging evaluation (Di Raimondo et al, 2007;Pavlović et al 2005) and has been indicated as an ''obligatory part of the staging procedure'' (Fischbach, 2010). Thus, in the 2010 ESMO guidelines (Zucca & Dreayler, 2010), EUS has been indicated as the most appropriate technique in defining the locoregional staging.…”
Section: Endoscopic Ultrasound In Staging Of Diseasementioning
confidence: 99%